Validasi skala penilaian instrumen perencanaan karier menggunakan Andrich Threshold - Sandjaja, Stefanus Soejanto; Syahputra, Yuda; Erwinda, Lira (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractSuccess in a career is synonymous with the welfare of an individual's life, which needs further handling from the counselor. In determining and preparing for a future career, counselors should use a valid and reliable inventory. However, inventory that is considered valid and reliable by the counselor still raises problems in administration, namely students are confused in setting the response point in the inventory. The purpose of this study is to find a clear and unambiguous rating scale to make it easier for students to set a response point in their inventory. The research sample uses area random sampling consisting of six groups of test subjects, namely: 1, n = 75; 2, n = 61; 3, n = 47; 4, n = 146; 5, n = 85; and 6, n = 63. Data in this study were 5-point Likert scale political data collected using career planning inventory. The research data were analyzed using the Rasch model by testing the rating scale analysis through Threshold analysis between ratings. The results showed the rating scale in the Threshold analysis, the rating scale changed to a four-point Likert scale with a choice of very inappropriate, not appropriate, appropriate, and very appropriate.Keywords: Career Planning; Likert Scale; Ratting Scale; Threshold AbstrakSukses dalam karier identik dengan kesejahteraan hidup individu, yang perlu penanganan lebih lanjut dari konselor. Dalam menentukan dan mempersiapkan karier dimasa depan, konselor mestinya menggunakan inventori yang valid dan reliabel. Namun, inventori yang dianggap valid dan reliabel oleh konselor masih memunculkan permasalahan dalam pengadministrasian, yaitu siswa bingung dalam menetapkan rating scale pada inventori. Tujuan penelitian ini adalah menemukan skala penilaian yang jelas dan tidak ambigu untuk memudahkan siswa menetapkan rating scale pada inventori. Sampel penelitian menggunakan area random samplingyang terdiri dari enam kelompok subjek tes, yaitu: 1, n = 75; 2, n = 61; 3, n = 47; 4, n = 146; 5, n = 85; dan 6, n = 63. Data dalam penelitian ini berupa data politomi 5-point Likert scale yang dikumpulkan menggunakan career planning inventory. Data penelitian dianalisis menggunakan model Rasch dengan menguji rating scale analysis melalui analisis Threshold antar rating. Hasil penelitian menunjukkan rating scale pada analisis Threshold, rating scale berubah menjadi empat point Likert scale dengan pilihan sangat tidak sesuai, kurang sesuai, sesuai, dan sangat sesuai. Kata kunci: Perencanaan Karier; Ratting Scale; Skala Likert; Threshold